EXPERIMENTAL AND MODELING OF FLOW OVER LABYRINTH AND PLAIN STEPPED FALLS - JALIL, SHAKER A.; HUSSEIN, BSHKOJ S. (Journal of Duhok University, 2017)
The characteristics of flow over plain and labyrinth stepped falls is investigated experimentally and simulated numerically using commercial package ANSYS CFX. The aim is to verify the numerical model by assessing its accuracy and dependence in modeling the flow over this kind of hydraulic structures. Eight physical models of rectangular labyrinth stepped fall cycles with general slope (1V:1H and 1V:2H), different step numbers (5 and 10) and two different cycle widths (0.06 and 0.1 m) were tested and simulated in laboratory flume. For the purpose of comparison four models of plain stepped falls are constructed with the same number of steps and slopes as the labyrinth ones, they were tested and simulated. The simulation is based on the RNG k-ε turbulence model, three dimensional volume of fluid method (VOF) and incompressible flows. To verify the numerical models, all experimental data including water surface profile, hydraulic head and total calculated energy dissipation were compared with the corresponding results predicted by the numerical model. The comparison showed good agreement between experimental and numerical results via applying statistical tests. The new labyrinth stepped fall model was more effective for dissipating the relative energy as compared with plain stepped falls. The results showed that with decreasing number of steps, downstream slope and increasing the length magnification ratio, the relative energy dissipation is increased. The numerical results illustrated that the local direction of flow depends on the depth of water on the steps and the width of the labyrinth cycle. Also it was observed that the local flow directions, which are occurred on streamlines and contours, are dependent on impingement angle of water velocity vectors which varies between 74 and 62.5 degree.